34=w-39

Simple and best practice solution for 34=w-39 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 34=w-39 equation:


Simplifying
34 = w + -39

Reorder the terms:
34 = -39 + w

Solving
34 = -39 + w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-1w' to each side of the equation.
34 + -1w = -39 + w + -1w

Combine like terms: w + -1w = 0
34 + -1w = -39 + 0
34 + -1w = -39

Add '-34' to each side of the equation.
34 + -34 + -1w = -39 + -34

Combine like terms: 34 + -34 = 0
0 + -1w = -39 + -34
-1w = -39 + -34

Combine like terms: -39 + -34 = -73
-1w = -73

Divide each side by '-1'.
w = 73

Simplifying
w = 73

See similar equations:

| 3-y=y+4 | | 3-y=y | | 72-4x=14x+16 | | -3(5x-3)= | | 4y+7=-1 | | 10(x+8)+5x=170 | | 4inx=-16 | | Logx(x+30)=2 | | 3+2(3x-6)=5-5(2x+1) | | 2y-7=19y+78 | | 84-4x=24+8x | | x+x*.11=165 | | 3x+47=8x-13 | | 3x+47=8x+13 | | 2x(4+x)=0 | | 8-7x+11+5x+3x-3=6+3*5 | | 6-3y=1-4y | | 3+5x=17-x | | z+1=-12 | | 3(2x-3)+x=12 | | 2(3x-5+x)=150 | | 6x+10=65+x | | -6p+42=12 | | 3a(2b-a+3)= | | 9m+5=87 | | (2x-5)+(x-5)=44 | | 9x+5=2x+6 | | f/9-25=-28 | | 5(2p+1)= | | 3x-15=10x-33 | | -2t^2+4t=0 | | x+2x+3x=2x+4 |

Equations solver categories